Queer subjects in modern Japanese literature male love, intimacy, and erotics, 1886-2014 - Miller, Stephen D. 1949- (Michigan monograph series in Japanese studies, 2022)
Queer Subjects in Modern Japanese Literature: Male Love, Erotics, and Intimacy, 1886–2014 is an anthology of translated Japanese literature about men behaving lovingly, erotically, and intimately with other men. Covering more than 125 years of modern and contemporary Japanese history, this book aims to introduce a diverse array of authors to an English-speaking audience and provide further context for their works. While no anthology can comprehensively represent queer Japanese literature, these selections nonetheless expand our understanding of queerness in Japanese culture